Fatmawati, Anisa UPAYA MENINGKATKAN ORAL ACTIVITY DAN KEMAMPUAN HOTS IPA MATERI ZAT TUNGGAL DAN ZAT CAMPURAN MELALUI MODEL READ-ANSWER-DISCUSS-EXPLAIN AND CREATE - Fatmawati, Anisa; Anggraeni, Poppy; Kusnandar, Nandang (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The research was undermined by the low oral activity and HOTS ability of students at SDN Sukasirna. One attempt to improve oral activity and HOTS ability of students is by using the learning model of RADEC. The research is aimed at finding out how to enhance oral activities and ability of HOTS IPA single and mixed substances through the RADEC model. This research uses the Class Action Research method (PTK). The research design used the Kemmis & Mc Taggart model carried out in two cycles, each cycle consisting of planning, implementation of observation and reflection. SDN Sukasirna's fifth grade of 29 students were the subject of his research. Observation techniques and test techniques are data collection techniques for this research. Model implementation sheets, oral activity observation sheet and evaluation tests become research instruments. The data analysis resulted that using the RADEC learning model, the percentage of oral activity in cycle 1 reached 69% with medium criteria and cycle 2 increased to 87% with very high criteria. The HOTS ability of students is also improved which is visible from the student's learning intensity in cycle I to 72% of the students who are in high school and at cycle II to 90%. Based on these findings, the conclusion can be drawn that the RADEC learning model can improve oral activity and the ability of HOTS students to learn single and mixed IPA materials.